MICROSURGICAL RECONSTRUCTION OF THE AERODIGESTIVE TRACT WITH COLONIC-ILEAL AUTOGENIC GRAFT IN PATIENTS WITH HYPOPHARYNX CANCER - M. V. Ratushny (Opuholi Golovy i Šei, 2015)
Study objective: development of the new method of reconstruction of upper section of the aerodigestive tract with the use of a microsurgical colonic-ileal autogenic graft that allows instant recovery of the food passage and voice function.A clinical case of successful treatment of a patient with locally distributed hypopharynx cancer is provided, regarding which microsurgical reconstruction of upper sections of the aerodigestive tract was performed with a free colonic-ileal autogenic graft at the surgical stage of therapy after laryngectomy with sleeve resection of the hypopharynx.The use of a colonic-ileal autogenic graft in the course of reconstruction of upper sections of the aerodigestive tract allowed instant recovery of both food passage and voice function for the patient after laryngectomy with sleeve resection of the hypopharynx.Conclusions:1. Application of this autogenic graft as a plastic material allows recovering both food passage and voice function instantly and completely with circular defects of upper sections of the aerodigestive tract.2. The ileocecal valve included into the structure of the combined autogenic graft prevents saliva and food aspiration into the trachea through the tracheo-oesophageal shunt.3. Mucous secretion of the autogenic graft has no aggressive action on the mucous membrane of the trachea, which allows implementation of the vocal rehabilitation plan.4. After the flap formation, there is no functional or aesthetic damage in the donor area.5. This reconstruction method cuts down the rehabilitation time significantly as well as decreases the patient’s disability level.